Soviet Lithuania and the Emigrė Community: a Project for Cultural Ties - Streikus, Arūnas (Lietuvos istorijos studijos, 2007)
The active search for cultural ties with Lithuanians in exile, which started in the middle 1960s, was a well planned action aimed at the strengthening of the Soviet regime. Its main purpose was not to start a genuine dialogue between two branches of Lithuanian culture, but to demonstrate the superiority of Soviet Lithuanian culture over the culture cherished in exile. The representation of emigre art and especially of intellectual works in Lithuania was very limited until the late 1980s and mostly connected with obtaining positive comments from emigre authors in regard to Soviet cultural policy. The spread of Soviet Lithuanian culture among emigres was clearly the main aim of cultural ties. The emigre community was disinformed by primarily presenting those creative works in which the symbols of the common national heritage subtly concealed a world outlook inspired by Soviet ideology. Thus, the appearance of a normal cultural life was imitated with the hope that it would help to win over the part of the emigre society, which had already lost the hope of the rapid restoration of statehood. Other different means were also used for disinformation: special publications in the exile press, infiltrations of KGB agents among persons who had close relations with famous exile cultural workers.Although the main aims the Soviet regime fostered in the field of cultural ties with the emigres were always the same, there were some changes in tactics. The quite large openness toward the exile community, which was characteristic for the first stage, from the middle of 1960s until 1972, died out later when the ideologisation of public life intensified. The attempts of liberal wing exile to use cultural ties as a way to enter into more close relations with the creative intelligentsia in Lithuania were discovered by the Soviet security rather quickly and more or less controlled. In 1970s and the early 1980s the main attention was directed to the communication with distinguished cultural workers living abroad. In the same period there were also attempts to set up a new centre, controlled by the Soviet regime, which could serve as the basis for cultural ties in the future. When such attempts failed and the regime became more open from the middle of 1980s, it started more boldly to establish ties with the liberal wing of the emigres again.
Keywords: -